Association between uveitis onset and economic development in mainland China - Handan Tan; Xiaojie Feng; Peizeng Yang (BMC, 2023)
Abstract Background Economic prosperity has fostered numerous changes that may translate into better or worse outcomes across all domains of health. This study aims to explore the associations of economic development with uveitis onset in mainland China. Methods We used Poisson regression with generalized estimated equations to quantify the associations of per capita gross domestic product (GDP) with uveitis onset in 31 provinces of mainland China from 2006 to 2017. We further estimated the effects mediated by economic growth on the temperature-uveitis and PM2.5-uveitis associations established in our previous studies. Results A total of 12,721 uveitis patients from 31 provinces of mainland China were studied. Overall, every 10,000 Chinese yuan ($ 1491.278, 2006-2017) increase in per capita GDP, with no weighted value or weighted by population, corresponded to 1.85% (95% confidence interval, 1.19-2.52%) and 1.43% (95% confidence interval, 0.37-2.51%) lnRR decrease in the uveitis onsets. Stratified analysis showed this negative association between per capita GDP and uveitis onset, only existed in male patients (P < .001), individuals aged 20-50 years (P < 0 .05), non-infectious uveitis, uveitis with systemic disease, and Bechet's disease (all P < 0 .05). Moreover, the increased per capita GDP, if above the national level, could reinforce both temperature-uveitis and PM2.5-uveitis association (both P < 0.001). Conclusions The findings suggest that economic development is negatively associated with uveitis onset. However, it may facilitate the uveitis onset mediated by both increased temperature and PM2.5 exposure if the per capita GDP is above national level.